An analysis of mergers in the presence of uncertainty in renewable energy integration costs - Daher, Wassim; Elnaboulsi, Jihad; Fikru, Mahelet G.; Gautier, Luis (ELSEVIER, 2025)
This study examines how uncertainty in renewable integration costs affects the profitability of mergers among energy producers. As the energy sector shifts toward decentralized renewables, centralized producers face industry-wide and firm-specific cost uncertainties due to the variable and intermittent nature of distributed generation. Although previous models have examined mergers in the presence of greener energy, they have largely assumed deterministic costs and ignored the impact of the dual sources of uncertainty on merger profitability. This study incorporates both industry-wide and private shocks into renewable integration costs, using two theoretical models – without and with uncertainty – to identify how these shocks affect merger profitability. With full information, we show that mergers are unprofitable unless they consolidate a majority of firms (e.g., 90% consolidation), where a higher renewable integration cost reduces losses from mergers. This is because joint profit maximization allows merger participants to better absorb (higher) costs while non-merging firms cut production more sharply. With uncertainty, we find that the effect of the two sources of uncertainties on merger profitability depends on the average grid integration cost, merger size, and quality of private information. In particular, results suggest that mergers are more likely to be profitable when firms can effectively absorb private shocks due to the merger size, unless average grid integration costs become too high. The incentives to merge are less clear-cut in the presence of an industry-wide shock, unless the quality of private information is high enough.
Keywords: Política energética; Electricidad - Mercados; Recursos energéticos renovables; Empresas - Fusión; Electricidad - Costes; Control de costes; Competencia económica; Riesgo (Economía); M&As; Green electricity; Grid integration cost; Signaling games; Cournot competition; Uncertainties